(untitled) (Research, Society and Development, 2021)
The research aims to study the legal action of consignment in payment as a means of effectiveness of objective good faith. Using the deductive method with doctrinal revision as a methodological option, the study of good faith begins as a vector of social conduct and concretization of the normative values of the legal order, aimed to demonstrate that ethical values permeate all contemporary legal systems, having been dedicated to procedural norms with a view to achieving justice that portrays an effective process. Next, the payment consignment lawsuit is analyzed as a means for the extinction of the obligations, with emphasis, among the hypotheses listed in article 335 of the Civil Code, to the creditor’s unjustified cause in receiving the payment of the obligation. After analyzing the delay accipiendi, as a basis for filing the payment consignment lawsuit and how the annexed duties in good faith can alter the legal relation and its filing, it is concluded that the payment consignment lawsuit, at the providing for suppressio and surrectio as a basis for the allegation of delay accipiendi, allows the debtor to release the mandatory bond through the systematic recurrence, constant and continuous of a certain behavior, taking the form of a means that gives effect to objective good faith.